Neurofibromin (NF1) genetic variant structure–function analyses using a full‐length mouse cDNA. Issue 6 (10th April 2018) - Wallis, Deeann; Li, Kairong; Lui, Hui; Hu, Ke; Chen, Mei‐Jan; Li, Jing; Kang, Jungsoon; Das, Shamik; Korf, Bruce R.; Kesterson, Robert A.
Abstract: Neurofibromatosis type 1 (NF1) is caused by pathogenic variants or mutations in the NF1 gene that encodes neurofibromin. We describe here a new approach to determining the functional consequences of NF1 genetic variants. We established a heterologous cell culture expression system using a full‐length mouse Nf1 cDNA ( mNf1 ) and human cell lines. We demonstrate that the full‐length murine cDNA produces a > 250 kDa neurofibromin protein that is capable of modulating Ras signaling. We created mutant cDNAs representing NF1 patient variants with different clinically relevant phenotypes, and assessed their ability to produce mature neurofibromin and restore Nf1 activity in NF1 −/− cells. These cDNAs represent variants in multiple protein domains and various types of clinically relevant predicted variants. This approach will help advance research on neurofibromin structure and function, determine pathogenicity for missense variants, and allow for the development of activity assays and variant‐directed therapeutics. Abstract : We established a heterologous cell culture expression system that allows structure‐function analyses of predicted NF1 patient mutations and variants of unknown significance using a full‐length mouse Nf1 cDNA and human cell lines. When the mNf1 cDNA is transiently transfected into HEK293 cells, neurofibromin is expressed in both NF1 replete ( NF1 +/+ ) and deficient ( NF1 −/− ) cells. Re‐expression of wild‐type mNf1 cDNAs, but not mutants, produces neurofibromin that suppresses elevated pERK seen in the NF1 −/− HEK293 cells.